The essence of public control over the activities of public authorities - Nironka, Yurii (Actual problems of law (Aktual'ni problemi pravoznavstva), 2019)
In the article essence is exposed and the qualificator features of public inspection are found out as an important constituent of mechanism of providing of constitutional principle of democracy. The institutional base of public inspection is outlined and it is indicated on her basic components. It is marked methods and forms of realization of public inspection from the side of citizens.Public control is defined as a type of social control as a function of civil society and a way of involving the population in the management of society and the state. It is an important form of the implementation of democracy, because it enables the population to participate in public administration, the decision of state and public affairs, and actively influence the activities of state authorities and local self-government.It is stressed that today an array of such methods of public control as observation is used; analysis of documents, official statistics; visits to the institution, examination of conditions; collecting complaints; interviews, interviews, focus groups; public expertise; monitoring, etc. The most important methods are monitoring and expertise.There are two main forms of exercising public control by citizens, which are enshrined in the Constitution of Ukraine the ability to exercise public control through public events; in the exercise of the right of citizens to form a public association as a means of influencing the state authorities and local self-government bodies or expressing a negative reaction to the policy implemented. The establishment of civil society institutions is accompanied by an extension of the mechanism of public control, which can provide them invaluable assistance and support in the implementation of state policy. Public control, organized and purposefully within the political and legal system, must solve the problems that arise between civilians and the state in a fully civilized way, through the use of channels of interaction and mutual responsibility, which are determined by law, and this control is the most important condition for the implementation of the constitutional principle of democracy.